Ascorbate attenuates red light mediated vasodilation: Potential role of S-nitrosothiols - Agnes Keszler; Brian Lindemer; Neil Hogg; Nicole L. Lohr (Redox Biology, 2019)
There is significant therapeutic advantage of nitric oxide synthase (NOS) independent nitric oxide (NO) production in maladies where endothelium, and thereby NOS, is dysfunctional. Electromagnetic radiation in the red and near infrared region has been shown to stimulate NOS-independent but NO-dependent vasodilation, and thereby has significant therapeutic potential. We have recently shown that red light induces acute vasodilatation in the pre-constricted murine facial artery via the release of an endothelium derived substance. In this study we have investigated the mechanism of vasodilatation and conclude that 670 nm light stimulates vasodilator release from an endothelial store, and that this vasodilator has the characteristics of an S-nitrosothiol (RSNO). This study shows that 670 nm irradiation can be used as a targeted and non-invasive means to release biologically relevant amounts of vasodilator from endothelial stores. This raises the possibility that these stores can be pharmacologically built-up in pathological situations to improve the efficacy of red light treatment. This strategy may overcome eNOS dysfunction in peripheral vascular pathologies for the improvement of vascular health.